Financial Literacy, Government Support, and Fintech Adoption as Drivers of SME Sustainability Performance - Irawan Irawan; Andueriganta Fadhlihi; Ina Rahmi Diwasya; Sri Astuti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid expansion of financial technology has reshaped financial practices among Micro, Small, and Medium Enterprises in Indonesia, particularly within the context of digital economic transformation. Specific Background In Bandar Lampung City, despite government digitalization initiatives, fintech utilization among MSMEs remains uneven, with persistent reliance on manual financial systems affecting sustainability outcomes. Knowledge Gap Existing technology adoption models insufficiently explain fintech adoption by MSMEs when institutional support, financial literacy, trust, and sustainability dimensions are jointly considered in a local Indonesian setting. Aims This study examines determinants of fintech adoption and evaluates its role in shaping MSME sustainability performance across economic, social, and environmental dimensions. Results Using a quantitative survey of 200 MSMEs and SEM-PLS analysis, financial literacy, government support, trust, perceived usefulness, and perceived ease of use were found to significantly shape fintech adoption, while user innovation showed no direct relationship. Fintech adoption demonstrated a strong association with sustainability performance. Novelty This study integrates Technology Acceptance Model constructs with institutional and sustainability perspectives to explain fintech adoption mechanisms in regional MSMEs. Implications The findings highlight the importance of coordinated government policies and financial literacy initiatives in fostering fintech-driven sustainability among MSMEs within emerging digital economies. Highlights: Multiple internal and institutional factors jointly explain digital financial system usage among small businesses. Digital financial system usage aligns with economic, social, and environmental business outcomes. Individual innovativeness alone does not translate into technology usage without supporting conditions. Keywords: Fintech, Financial Literacy, Government Support, User Innovation, Sustainability Performance, MSMEs